2010
DOI: 10.1248/bpb.33.415
|View full text |Cite
|
Sign up to set email alerts
|

Gambogenic Acid Inhibits Proliferation of A549 Cells through Apoptosis-Inducing and Cell Cycle Arresting

Abstract: Although anticancer effect of gambogic acid (GA) and its potential mechanisms were well documented in past decades, limited information is available on the anticancer effect of gambogenic acid (GNA), another major active component of Gamboge. Here we performed a study to determine whether GNA possesses anticancer effect and find its potential mechanisms. The results suggested that GNA significantly inhibited the proliferation of several tumor cell lines in vitro and in vivo. Treatment with GNA dose and time de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
68
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 18 publications
3
68
0
Order By: Relevance
“…GNA has been confirmed as the anti-tumor component of the traditional Chinese drug cambogia (Lei et al, 2003). Accumulating evidence indicates that GNA has a potential anti-tumor effect in many tumor cells (Li et al, 2010;Chen et al, 2012;Yan et al, 2012), but only Li et al demonstrated that GNA inhibited tumor growth in A549 xenograft nude mouse models (Li et al, 2010). In order to determine whether GNA plays an anti-tumor role in other tumors in vivo, MDA-MB-231 cell, an aggressive breast cancer cell line, was been chosen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GNA has been confirmed as the anti-tumor component of the traditional Chinese drug cambogia (Lei et al, 2003). Accumulating evidence indicates that GNA has a potential anti-tumor effect in many tumor cells (Li et al, 2010;Chen et al, 2012;Yan et al, 2012), but only Li et al demonstrated that GNA inhibited tumor growth in A549 xenograft nude mouse models (Li et al, 2010). In order to determine whether GNA plays an anti-tumor role in other tumors in vivo, MDA-MB-231 cell, an aggressive breast cancer cell line, was been chosen.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, we did not continue to investigate the detail signaling pathways. Li et al have reported that GNA can inhibit A549 cell proliferation through apoptosis by inducing the up-regulation of the p38 MAPK cascade and cell cycle arrest (Li et al, 2010;Yan et al, 2012). Chen et al found that GNA induced time-and dose-dependent growth inhibition and apoptosis Akt pathway inactivation in U251 glioblastoma cells (Chen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gamboge, a well-known herbal medicine derived from the Garcinia hanburyi tree, shows widely pharmacological activities including detoxification, anti-inflammatory and parasiticide effects (Asano et al, 1996;Li et al, 2010). Its main active components includes gambogenic acid (GNA, Figure 1a) and gamboge acid (GA, Figure 1b), and GNA exhibits stronger and broader pharmacological activities (Zhou et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Available evidence suggests that GNA being the best representative, has the most potential of broad spectrum anticancer drug candidate, which has shown to have a strong anti-tumor activity against gastric carcinoma, hepatoma, breast cancer and lymphatic sarcoma in vitro and in vivo (Li et al, 2010), which mostly attributes that GNA is capable in arresting the cancerous cells to G 0 /G 1 with regulating expression of cyclin D1 and cyclo-oxygenase(COX)-2 (Yan et al, 2011). However, its therapeutic potential has been restricted mainly due to its irritation to the blood vessel, very low aqueous solubility and poor bioavailability or toxicity profiles.…”
Section: Introductionmentioning
confidence: 99%